ANALISIS KESALAHAN BERBAHASA PADA PENULISAN MEDIA LUAR RUANG DI KABUPATENBOJONEGORO - Hasanudin, Cahyo (Universitas Pendidikan Indonesia, 2017)
This research aims at: 1) describing the errors of writing in bahasa Indonesia in outdoor media in Bojonegoro, 2) describing the errors in using foreign elements, and 3) determining the suitability of the results of research with teaching materials of bahasa Indonesia at Junior High School. This research is qualitative descriptive with a sample of articles in outdoor media in Bojonegoro. The sampling technique used was purposive. Data collection techniques used were recording, observation, and note-taking. Data validation techniques used were triangulation and peer assessment. The data analysis technique was an interactive analysis which includes four components, namely data collection, data reduction, data presentation, and verification. The conclusions of this study are as follows. First, the linguistic elements of language errors in outdoor media are related to the use of punctuations, especially a period (.), writing the preposition of â€œdiâ€, the use of the word â€œpukulâ€ and â€œjamâ€, and abbreviations. Secondly, the type of improper use of foreign terms is dominated by the use of the English and the Javanese. Both languages are used simultaneously on any word or Indonesian phrase. Third, the result of this research can be used as teaching materials of bahasa Indonesia at junior high school level, especially on the subject of spelling and foreign terms (borrowing).Keywords: language error, outdoor media, spelling, foreign terms, teaching materials